Redesign User Interface at PT. Budi Jaya Banjarindo Using UCD Method - Ariansyah, Doddy; Paputungan, Irving Vitra (Jurnal Sains, Nalar, dan Aplikasi Teknologi Informasi, 2024)
Budi Jaya Banjarindo operates in the machining and manufacturing sector and has a production system (make to order), which means the product is made according to consumer requests or design. This company uses machine equipment such as lathes, CNC machines, CNC Plasma Cutting, milling machines, hobbing and so on. Evaluation and redesign of the user interface system using Figma tools which will later be used by the workshop to optimize online product marketing. The system was designed using the UCD method. The final design result is a prototype which will then be assessed or tested using the SUS method to obtain an assessment from users. The SUS Score obtained was 65, based on these results it is included in the C range (range 60-70). These results indicate that the UI evaluation results are of good quality. The conclusion of redesigning the interface by adding several additional features, successfully meets user needs and the quality of test results is good.